Prognosis assessment of persistent left bundle branch block after TAVI by an electrophysiological and remote monitoring risk-adapted algorithm: rationale and design of the multicentre LBBB–TAVI Study. Issue 10 (26th October 2016) - Massoullié, Grégoire; Bordachar, Pierre; Irles, Didier; Caussin, Christophe; Da Costa, Antoine; Defaye, Pascal; Jean, Frédéric; Mechulan, Alexis; Mondoly, Pierre; Souteyrand, Géraud; Pereira, Bruno; Ploux, Sylvain; et al.
Abstract : Introduction: Percutaneous aortic valve replacement (transcatheter aortic valve implantation (TAVI)) notably increases the likelihood of the appearance of a complete left bundle branch block (LBBB) by direct lesion of the LBB of His. This block can lead to high-grade atrioventricular conduction disturbances responsible for a poorer prognosis. The management of this complication remains controversial. Method and analysis: The screening of LBBB after TAVI persisting for more than 24 hours will be conducted by surface ECG. Stratification will be performed by post-TAVI intracardiac electrophysiological study. Patients at high risk of conduction disturbances (≥70 ms His–ventricle interval (HV) or presence of infra-Hisian block) will be implanted with a pacemaker enabling the recording of disturbance episodes. Those at lower risk (HV <70 ms) will be implanted with a loop recorder device with remote monitoring of cardiovascular implantable electronic devices (CIEDs). Clinical, ECG and implanted device follow-up will also be performed at 3, 6 and 12 months. The primary objective is to assess the efficacy and safety of a decisional algorithm based on electrophysiological study and remote monitoring of CIEDs in the prediction of high-grade conduction disturbances in patients with LBBB after TAVI. The primary end point is to compare the incidence (rate and time to onset) of high-grade conduction disturbances in patients with LBBB after TAVI between the two groups at 12 months. Given the proportion of high-grade conduction disturbances (20–40%), a sample of 200 subjects will allow a margin of error of 6–7%. The LBBB–TAVI Study has been in an active recruiting phase since September 2015 (21 patients already included). Ethics and dissemination: Local ethics committee authorisation was obtained in May 2015. We will publish findings from this study in a peer-reviewed scientific journal and present results at national and international conferences. Trial registration number: NCT02482844; Pre-results.